Basal cell carcinoma: 10-year experience with electrochemotherapy - Luca G. Campana; Roberto Marconato; Sara Valpione; Sara Galuppo; Mauro Alaibac; Carlo R. Rossi; Simone Mocellin (Journal of Translational Medicine, 2017)
Abstract Background Electrochemotherapy (ECT), by combining manageable cytotoxic agents with short electric pulses, represents an effective palliative skin-directed therapy. The accumulated evidence indicates that ECT stands out as a safe and well-tolerated alternative treatment for patients with multiple or large basal cell carcinoma (BCC), who are not suitable for conventional treatments. However, long-term data and shared indications are lacking. Methods In this observational study, we retrospectively analyzed 84 prospectively collected patients with multiple, recurrent or locally advanced BCC who were not candidate for standard therapies and received bleomycin-based ECT according to the European Standard Operative Procedures of ECT, from 2006 to 2016. Results Disease extent was local, locally advanced and metastatic in 40 (48%), 41 (49%) and 3 (3%), respectively. Forty-four (52%) individuals had multiple BCCs. Grade 3 skin toxicity after ECT was observed in 6% of cases. Clearance rate was 50% (95% CI 39–61%). Primary presentation (p = 0.004), tumor size <3 cm (p < 0.001), well-defined borders (p = 0.021), absence of tumor ulceration (p = 0.001), non-aggressive BCC histology (p = 0.046) and age ≤69 years were associated with higher complete response rate. In patients with local BCC, the clearance rate was 72.5 and 85% after one or two ECT cycles, respectively. In the laBCC group, 32 patients (78%) achieved an objective response. Five-year recurrence rate for local and laBCC was 20 and 38%, respectively (p ≤ 0.001). Conclusions One or two ECT cycles with bleomycin may be a valuable palliative treatment in well-selected patients with multiple BCCs and favorable tumor features. Validation of predictive factors will be imperative to match patients with optimal ECT treatment modalities. Management of laBCC with ECT warrants further investigation. Trial registration ISRCTN14633165 Registered 24 March 2017 (retrospectively registered)